Comprehensive Review of the Genetic Polymorphism of Schistosoma mansoni and Drug Resistance: Human vs. Intermediate Host Perspective - Zinab Ahmed Sonpul et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Schistosoma mansoni, the causative agent of intestinal schistosomiasis, exhibits substantial genetic polymorphism, contributing to its adaptability and resistance to praziquantel (PZQ), the mainstay treatment for schistosomiasis. This review explores the genetic mechanisms underlying S. mansoni diversity, emphasizing its role in drug resistance and interactions with human (definitive) and snail (intermediate) hosts. Genetic variation in S. mansoni is driven by sexual reproduction, recombination, and host-parasite co-evolution, with key contributions from microsatellites, mitochondrial DNA, and single nucleotide polymorphisms (SNPs). While human immune responses and PZQ administration impose selective pressures, snail hosts shape genetic compatibility and transmission dynamics. Evidence suggests that high genetic diversity enhances immune evasion and influences drug susceptibility, complicating control efforts. Comparative analysis of human and snail host influences reveals distinct yet interconnected drivers of parasite evolution. Integrative strategies combining genomic surveillance, snail control, and novel therapeutics are essential for managing drug resistance and sustaining schistosomiasis control efforts. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/289 DOI: https://doi.org/10.5281/zenodo.14549331